Making sense of an historic landscape - Rippon, Stephen 1968- (Oxford University Press, 2012)
This volume explores how the archaeologist or historian can understand variations in landscapes. Making use of a wide range of sources and techniques, including archaeological material, documentary sources, and maps, Rippon illustrates how local and regional variations in the 'historic landscape' can be understood.